Perancangan Catu Daya Berbasis Up-Down Binary Counter Dengan 32 Keluaran - Rifaldi Yanis; Dringhuzen J. Mamahit; Ellia K. Allo; Sherwin R.U.A. Sompie (Jurnal Teknik Elektro dan Komputer, 2013)
With the rapid development of technology in the field of power electronics in particular, people are aware that there are things that can hurt one is the more expensive price of the components used. The power supply is frequently encountered today are generally still in shape and still in analog processes ana the level of accuracy that has not been right so often goes wrong in determining the value of voltage. For this reason, it can be designed a power supply with a digital process. In designing these tools, the authors make use of simple components of electronics are usually found in the market and some of the supporting components in engineered a power supply. The power supply can be used to supply DC voltage to a particular object with a combination of 5-bit binary number. To support the necessary labor supply additional system such as ATmega 8535 AVR for voltage value on the LCD display. The ability of the power supply is capable of supplying voltages of an object or a specific load of recommended input voltage up to 32 volts and maximum current of 3 amperes and stabel to be able to distribute the load has a power of 28 watt. Keywords : Binary, Counter,  DC Voltage, Power Supply. Seiiring perkembangan teknologi yang semakin pesat dalam bidang elektronika khususnya catu daya, manusia menyadari bahwa masih terdapat hal yang merugikan. Salah satunya adalah makin mahalnya harga komponen-komponen yang digunakan. Catu daya yang sering kita jumpai saat ini pada umumnya masih dalam bentuk dan proses yang masih secara analog dan tingkat keakuratannya yang belum tepat sehingga sering terjadi kesalahan dalam menentukan nilai tegangan. Karena alasan ini, maka dapat dirancang suatu catu daya dengan proses secara digital. Dalam merancang alat ini, penulis memanfaatkan komponen-komponen sederhana yang merupakan komponen-komponen dasar elektronika yang biasa dijumpai di pasaran dan beberapa komponen penunjang dalam merekayasa suatu catu daya. Catu daya tersebut dapat digunakan untuk mensuplai tegangan DC untuk suatu objek tertentu dengan kombinasi bilangan binary 5-bit. Untuk menunjang kerja catu daya diperlukan sistem-sistem tambahan seperti AVR ATmega8535 untuk menampilkan nilai tegangan pada LCD. Keywords : Binary, Counter,  DC Voltage, Power Supply.